Unlocking Descriptive Writing Skills with Picture Word Inductive Model (PWIM): A Study with Tenth-Grade Students at SMK Negeri 1 Sungai Tebelian - Ilinawati, Ilinawati; Dharma, Yokie Prasetya; Irawandi, Hery (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This Classroom Action Research (CAR) study explores the effectiveness of the Picture Word Inductive Model (PWIM) in improving tenth-grade students' descriptive writing skills and classroom participation at SMK Negeri 1 Sungai Tebelian in the 2023/2024 academic year. The research aimed to evaluate how PWIM, a student-centered approach involving visual aids and inductive reasoning, influenced students' engagement and writing outcomes over two cycles. Data were collected from a variety of sources, including classroom observations, field notes, writing tests, student interviews, and video recordings, which provided both quantitative and qualitative insights. In the first cycle, despite the introduction of PWIM, students were hesitant and passive, resulting in average writing scores and limited participation. Observations revealed that students were unsure about the new approach and lacked confidence. To address these issues, several instructional adjustments were made for the second cycle, including providing additional scaffolding, promoting group discussions, and offering more explicit modeling of writing tasks. These changes contributed to an improved classroom atmosphere where students felt more comfortable and confident. The second cycle showed significant improvements. Student participation rose from 69.95% in Cycle I to 77.62% in Cycle II, reflecting a more active and engaged class. Writing scores also improved, with the average score increasing from 68.15 to 75.6, representing a 10.93% improvement. Interviews with students revealed that visual aids helped them generate ideas and write more detailed descriptive texts, boosting their writing fluency. This study concludes that PWIM is an effective method for enhancing both participation and writing skills in descriptive text learning. The findings highlight the importance of teacher adaptability and reflective practice in achieving sustained improvements in student performance. These insights offer valuable guidance for educators seeking innovative, research-based strategies to enhance writing instruction